Investigation of physical and chemical properties of potential edible and non-edible feedstocks for biodiesel production, a comparative analysis - Atabani A.E.; Mahlia T.M.I.; Anjum Badruddin I.; Masjuki H.H.; Chong W.T.; Lee K.T. (Elsevier Ltd, 2023)
Recently, non-edible vegetable oils have been considered as prospective feedstocks for biodiesel production. This is mainly attributed to their ability to overcome the problems of food versus fuel crisis related to edible oils. Globally, there are more than 350 oil-bearing crops identified as potential sources for biodiesel production. The evaluation of the physical and chemical properties of non-edible feedstocks is very important to assess their viability for future biodiesel production. Therefore, this paper aims to study the properties of some potential non-edible feedstocks. Moreover, the paper studies the physical and chemical properties of these promising crops and compares them with other edible oils. These oils include: crude Calophyllum inophyllum L. (CCIO), Jatropha curcas L. (CJCO), Sterculia foetida L. (CSFO), Croton megalocarpus L. (CCMO), Moringa oleifera L. (CMOO), patchouli (CPO), coconut (CCO), palm (CPaO), canola (CCaO), soybean (CSO) and Pangim edule (CPEO) oils. 14 Different properties have been determined and presented in this study. 2013 Elsevier Ltd.